Primary Frequency Regulation with Load-Side Participation-Part II: Beyond Passivity Approaches - Devane, Eoin; Kasis, Andreas; Antoniou, Marina; Lestas, Ioannis (My University, 2017)
We consider the problem of distributed generation and demand control for primary frequency regulation in power networks, such that stability and optimality of the power allocation can be guaranteed. It was shown in Part I of this work, that by imposing an input strict passivity condition on the net supply dynamics at each bus, combined with a decentralized condition on their steady-state behavior, convergence to optimality can be guaranteed for broad classes of generation and demand control dynamics in a general network. In this paper, we show that by taking into account additional local information, the input strict passivity condition can be relaxed to less restrictive decentralized conditions. These conditions extend the classes of generation and load dynamics for which convergence to optimality can be guaranteed beyond the class of passive systems, thus, allowing to reduce the conservatism in the analysis and feedback design.
Keywords: Stability; Frequency control; Decentralized control